Life Before Life: Is There Life Before Birth 750 Cases of Hypnosis by Helen Wambaugh - Hayen, Todd (Journal of Scientific Exploration, 2021)
This book was originally published in 1979. This reviewer is not certain why it has been re-published in 2020—possibly because a very popular, relatively current, text by Dr. Jim Tucker of the same name has been on the market since 2008—of course a reprint of a past life research classic is always welcome. The current book by Helen Wambach being reviewed is also quite different from Tucker’s and consists of a compilation of answers from individual questionnaires (750) filled out by participants who gathered for a group workshop in Chicago with Dr. Wambach. Nearly all of the data that Wambach analyzes was acquired though these questionnaires which were distributed to the participants of the workshop after undergoing extensive hypnosis. The book begins with an introduction where Wambach shares a bit of her history as a psychologist and researcher in the field of past life regression hypnosis. The reader must keep in mind she wrote this book in 1979 regardless of the 2020 copyright and the “new release” feel of the book. 1979 was over 40 years ago and quite a few advances have been made in both medical science (she mentions her interest in doing work in the area of biofeedback “so we can begin to relate specific EEG recordings with subjective phenomena experienced…” (Wambach, 2020, p. 7)) as well as past life regression work. Although not a serious hindrance in assimilating the material she presents, it is something worth keeping in mind while reading Life Before Life.